Ingestion of triglycerides containing medium- and long-chain fatty acids can increase metabolism of ingested long-chain triglycerides in overweight persons - Nosaka, Naohisa; Tsujino, Shogo; Sadamitsu, Shohei; Ando, Nanaka; Kato, Kazuhiko (Frontiers in Nutrition, 2023)
Introduction Medium-chain fatty acids (MCFAs) have attracted considerable attention for preventing or improving obesity, which is a recognized risk factor for lifestyle-related diseases. Medium- and long-chain triglycerides (MLCTs) are expected to improve the metabolism of ingested long-chain triglycerides (LCTs). However, previous studies have reported mixed results. In this study, the effect of ingestion of MLCTs was evaluated on the metabolism of LCTs and compared to the ingestion of rapeseed oil (control oil). Methods A randomized, double-blind, placebo-controlled crossover study was performed among sedentary participants with BMIs ranging from 25 below 30 kg/m2. Thirty participants were asked to ingest either 14 g of MLCTs or a control oil for 4 weeks. The metabolism of ingested LCTs was evaluated by measuring isotopically labeled carbon dioxide released by the degradation of carbon-13 (13C)-labeled LCTs. Results Ingestion of MLCTs markedly enhanced the metabolism of ingested LCTs by comparison to the control oil. Conclusion The findings of this study suggest that ingestion of MLCTs may enhance the metabolism of dietary LCTs through activation of β-oxidation in liver mitochondria, which may increase the metabolic kinetics of ingested long-chain fatty acid (LCFAs). Clinical trial registration https://center6.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000053101, identifier: UMIN000046604.